(untitled) (Medical Forum Monthly, 2023)
Objective: To find out the effectiveness and experiences of students with adaptive online TBL strategy utilized during COVID-19 lockdowns. Study Design: Cross-sectional study Place and Duration of Study: This study was conducted at the Jinnah Sindh Medical University from 1st December to 31 December 2020. Materials and Methods: A total of 177 students were included in the study. After taking permission from the institutional review board, a link to consent and questionnaire was sent to the students. The questionnaire was divided into software and TBL related questions. Results: The mean score for the section on software was 3.9 while for TBL activity was 3.6. When students were asked about their experience with the activity, they responded good (47.5%) for working as a team and for communication with colleagues and faculty as good (42.9%) while only 32.5% of the students scored 3 out of 5 for their satisfaction with the online TBL strategy. Overall, 50.8% agreed that online TBL sessions helped clarify their concepts and 46.9% agreed that they will like future online TBL sessions. Conclusion: Students were satisfied with their online TBL sessions and appreciated the different aspects of the strategy such as working as a team, motivation, and communication resulting in clarification of concepts.